Cold weather is independently associated with hypothermia in severely injured trauma patients. (January 2022) - Murphy, Colin; Silva, Noah; Fontaine, Magali J; Jackson, Bryon
Introduction: Hypothermia at admission in trauma patients has been significantly associated with worse outcomes and increased blood usage. Previous studies have found variably significant associations between ambient temperatures and incidence of hypothermia in trauma patients. Methods: The trauma quality improvement registry was queried for data on trauma patients admitted direct from the scene over a 5-year period. This database was matched to daily weather data taken from the nearest National Oceanic and Atmospheric Administration land-based climate monitoring center, and further combined with blood usage data from the laboratory information system. Results: Multivariate logistic regression models predicted significant associations between ambient temperature and patient admission temperature for severely injured patients. No significant direct associations were predicted between ambient temperature and in-hospital mortality or blood usage. Models predicted a significant association between decreased admission temperature and increased likelihood of both blood transfusion and mortality for a severely injured subgroup. Conclusions: Ambient temperature is a significant contributor to the rate of admission hypothermia in trauma patients. Most of the variability in admission temperatures for severely injured trauma patients remains unaccounted for by models using standard markers of anatomic and physiologic severity. Decreasing admission temperature is significantly associated with increased mortality and likelihood of blood transfusion for severely injured patients.